Effects of Kyrgyzstan’s evolution from the socialist into the new marketing system-customers and salespeoples perception changes in transition period - Orunbaev, İslamidin (My University, 2003)
Bu çalışmanın amacı Kırgızistan'daki şirketlerin geçiş aşamasındaki pazarlama organizasyonlarını anlamaya ve bu şirketlerin muşterilerilerine mal ve hizmet sunmaya yönelik faaliyetlerinin başarı göstergelerini öşçmeye yöneliktir. Çalışmada uygulama alanı olarak pazarlamanın birçok unsurunu içeren alışveriş merkezleri seçilmiştir. Çalışma teorik bulguları ve Kırgızistan piyasasında 2001 yılında yapılan araştırma sonuçlarını içermektedir. Çalışma, Giriş ve Sonuç bölüleri dahil olmak üzere 6 bölümden oluşmaktadır. Giriş bölümünde anahatlarıyla Kırgızistan piyasasının statüsü açıklnmış, çalışmanın amacı ve önemi üzerinde durulmuştur. İkinci bölümde Kırgızistan merkezi planlama dönemindeki sosyalist çevrede var olan pazarlama anlayışına yer verilmiştir. Bu bölümde sosyalizm dönemindeki mal ve hizmet anlayışı, fiyatlama stratejisi, dağıtım sistemi ve promosyon uygulamaları incelemeye çalışılmıştır. Üçüncü bölümde Kırgızistandaki serbest piyasaya geçiş dönemindeki gelişmeler, günümüzdeki global dünyadaki mal ve hizmet anlayışı, fiyatlama stratejisi , dağıtım sistemi ve promosyon uygulamaları açıklanmıştır. Dötdüncü bölümde araştırmanın metodolojisine yer verilmiştir. Beşinci bölümde araştırmanın bulguları yer almaktadır. Son bölümde Kırgızistan'ın başkenti olan Bişkekek şehrinde 2001 yılının Haziran ayında 199 müşteri üzerinde yapılan araştırma sonuçları yer almaktadır.

This study is aimed to understand the organization for marketing among companies of Kyrgyzstan during transition period and to measure the actual performance of these companies in satisfying expectations of customers as shopping centers which render range of products and services. The field of study is based on questionnaire survey that was conducted to examine marketing mix components and the properties of the shopping centers which render range of product and services. The study includes the literature review on related issues and survey on Kyrgyzstan market conducted in 2001. This study consists of six chapters including introduction and conclusion. In the introduction part the status of Kyrgyzstan market is described in a general framework and the objectives and the importance of the study are outlined. The second chapter emphasizes the marketing in socialist environment, the days of central planning: approaches to the product and services, pricing strategy, distribution system, promotion application and the role of stores, salespeople in the socialist system. The third chapter emphasizes the evolution of marketing in Kyrgyzstan toward a free market economy and the marketing in todays global world, marketing mix, product and services, pricing strategy, distribution system and promotion application described. The fourth chapter emphasizes research methodology and design of the field study conducted. The information on study's problem and objectives, data collection method and instrument, sampling plan, hypotheses stated, and analysis methods are presented. The fifth chapter includes findings of the research provided. The last chapter is reserved for the survey conducted on 199 respondents in june 2001 İn Bishkek , Kyrgyzstan
Keywords: Kırgızistan_Ekonomik Durum; Pazarlama